Identification of QTL associated with cold acclimation and freezing tolerance in Zoysia japonica. Issue 5 (12th January 2021) - Brown, Jessica M.; Yu, Xingwang; Holloway, H. McCamy P.; Tuong, Tan D.; Schwartz, Brian M.; Patton, Aaron J.; Arellano, Consuelo; Livingston, David P.; Milla‐Lewis, Susana R.
Abstract: Zoysiagrasses ( Zoysia spp.) are relatively low‐input and warm‐season turfgrasses which have grown in popularity in the United States since their introduction in the 1890s. Over 30 improved zoysiagrass cultivars were released in the past three decades, but many lack freezing tolerance and their use is limited to warm‐humid climates. Understanding the genetic controls of winter hardiness and freezing tolerance in zoysiagrass could considerably benefit the breeding efforts to increase tolerance to freezing stress. In the present study, controlled environment acclimation and freezing tests were used to evaluate a Meyer × Victoria zoysiagrass mapping population for post‐freezing surviving green tissue (SGT) and regrowth (RG). Quantitative trait loci (QTL) mapping analysis identified nine QTL associated with SGT, eight QTL linked to RG, and 22 QTL common in both traits, accounting for between 6.4 and 12.2% of the phenotypic variation. Eleven regions of interest overlapped with putative winter injury QTL identified in a previous field study. Upon sequence analysis, homologs of several abiotic response genes were found underlying these overlapping QTL regions. The homologs of these gene encode transcription factors, cell wall modification‐related proteins, and defense signal transduction‐related proteins. After further validation, these QTL and their associated markers have potential to be used in future breeding efforts for the development of a broader pool of zoysiagrass cultivars capable of surviving in cold climates.